Freedom and the Cage : Modern Architecture and Psychiatry in Central Europe, 1890-1914 - Topp, Leslie, 1969- (Book collections on Project MUSE., 2017)
"Explores the issues surrounding the architectural design of insane asylums in the late nineteenth-century Habsburg Empire, including the paradox of maximizing individual freedom within an environment of involuntary confinement"--Provided by publisher